2022
DOI: 10.1017/s0031182022000063
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in a recent transmission region: 27.4% infectivity rate among seronegative dogs

Abstract: American visceral leishmaniasis (VL) is a parasitic disease whose main domestic reservoir in the urban environment is dog and is considered one of the most important zoonoses in the context of public health. Serological tests are typically used for the diagnostic screening of the disease. This study aimed to analyse the performance of different methodologies used in the diagnosis of VL in dogs sampled from a recent transmission area. The sample consisted of 52 dogs separated into groups based on the absence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…False-negative results are high when a screening test presents a relatively low sensitivity value. In this same study, carried out in Lavras, a municipality adjacent to Ribeirão Vermelho, Gondim et al (2022) found that more than half of the infected dogs did not display clinical signs characteristic of VL and were no longer detected by the screening tests. This finding is particularly important since dogs without clinical signs can present high transmissibility and potential for maintenance and dissemination of the parasite (Tolezano et al 2007).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…False-negative results are high when a screening test presents a relatively low sensitivity value. In this same study, carried out in Lavras, a municipality adjacent to Ribeirão Vermelho, Gondim et al (2022) found that more than half of the infected dogs did not display clinical signs characteristic of VL and were no longer detected by the screening tests. This finding is particularly important since dogs without clinical signs can present high transmissibility and potential for maintenance and dissemination of the parasite (Tolezano et al 2007).…”
Section: Discussionmentioning
confidence: 81%
“…It is still important to emphasize that the screening tests recommended by the "Ministério da Saúde" provide heterogeneous data and may present false negatives, even though these tests have high sensitivity. Gondim et al (2022) found low sensitivity in immunochromatographic tests used for screening. False-negative results are high when a screening test presents a relatively low sensitivity value.…”
Section: Discussionmentioning
confidence: 98%
“…Since these 16 dogs tested negative in all analyses other than the test on the conjunctival swab in the follow-up period, we ran a second statistical analysis excluding all dogs of this household. Reverse transcription-qPCR (qRT-PCR) on conjunctival swabs has proven to be a very sensitive non-invasive technique to screen dogs for leishmaniosis, as it has the potential to detect infection earlier than if it were performed on other tissues, even before any symptoms become evident [ 21 23 ]. However, it has been suggested that a positive result only by qRT-PCR on conjunctival swabs, in the absence of a positive result with any other diagnostic test or the presence of any clinical sign, should be considered with caution [ 24 ].…”
Section: Discussionmentioning
confidence: 99%